(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The question of future energy-efficient creation of living space is becoming more and more important in many cities due to limited space availability and simultaneously increasing settlement pressure. Against the background of the desired space, resource and energy efficiency, cities are steadily-focusing on internal development and densification. In order to encourage a sustainable urban development, the existing densification potentials need to be mobilized by addressing the owners directly, to convince them for the measures to mobilize the given potentials. Therefore innovative GIS methods and databases are used within the research projects “BONSEI!” and “BONUS” in order to detect these potentials. Following is a gradually constructive consultation that helps house owners, depending on their needs and wishes, to find potential construction actions to increase the living space within their parcel. The research project “BONUS” further tackles problems and concerns, which come with densification, by maintaining high quality green spaces and at the same increase the usage of sustainable forms of mobility and try to reduce car usage within the districts.